Stabilizing DNA–Protein Co-Crystals via Intra-Crystal Chemical Ligation of the DNA - Abigail R. Orun; Sara Dmytriw; Ananya Vajapayajula; Christopher D. Snow (Crystals, 2021)
Protein and DNA co-crystals are most commonly prepared to reveal structural and functional details of DNA-binding proteins when subjected to X-ray diffraction. However, biomolecular crystals are notoriously unstable in solution conditions other than their native growth solution. To achieve greater application utility beyond structural biology, biomolecular crystals should be made robust against harsh conditions. To overcome this challenge, we optimized chemical DNA ligation within a co-crystal. Co-crystals from two distinct DNA-binding proteins underwent DNA ligation with the carbodiimide crosslinking agent 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC) under various optimization conditions: 5′ vs. 3′ terminal phosphate, EDC concentration, EDC incubation time, and repeated EDC dose. This crosslinking and DNA ligation route did not destroy crystal diffraction. In fact, the ligation of DNA across the DNA–DNA junctions was clearly revealed via X-ray diffraction structure determination. Furthermore, crystal macrostructure was fortified. Neither the loss of counterions in pure water, nor incubation in blood serum, nor incubation at low pH (2.0 or 4.5) led to apparent crystal degradation. These findings motivate the use of crosslinked biomolecular co-crystals for purposes beyond structural biology, including biomedical applications.